Rethinking Short-Chain Fatty Acids: A Closer Look at Propionate in Inflammation, Metabolism, and Mucosal Homeostasis - Sonia Facchin; Matteo Calgaro; Edoardo V. Savarino (Cells)
Propionate is a short-chain fatty acid (SCFA) produced by gut microbiota through the fermentation of dietary fibers. Among the SCFAs, butyrate stands out and has been extensively studied for its beneficial effects; however, propionate has received less attention despite its relevant roles in immune modulation, metabolism, and mucosal homeostasis. This narrative review focuses on propionate’s effects on metabolism, inflammation, microbiota, and gastrointestinal diseases. Propionate acts as a signalling molecule through FFAR2/FFAR3 receptors and modulates immunity, energy metabolism, and gut–brain communication. It has beneficial effects in metabolic disorders, inflammatory bowel disease (IBD), and alcohol-related liver disease (ALD). However, excessive accumulation is linked to neurotoxicity, autism spectrum disorder (ASD), and mitochondrial dysfunction. Its effects are dose-dependent and tissue-specific, with both protective and harmful potentials depending on the context. Propionate use requires a personalized approach, considering the pathological context, host microbiota composition, and appropriate dosage to avoid adverse effects.